2019
DOI: 10.1101/2019.12.20.883835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole-body imaging of neural and muscle activity during behavior inHydra: bidirectional effects of osmolarity on contraction bursts

Abstract: The neural code relates the activity of the nervous system to the activity of the muscles to the generation of behavior. To decipher it, it would be ideal to comprehensively measure the activity of the entire nervous system and musculature in a behaving animal. As a step in this direction, we used the cnidarian Hydra vulgaris to explore how physiological and environmental conditions alter the activity of the entire neural and muscle tissue and affect behavior. We used whole-body calcium imaging of neurons and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…In smaller, transparent animals such as larval zebrafish, C. elegans, and hydra, activity of the majority of neurons can be imaged simultaneously at cellular resolution in the fully intact animal (Ahrens et al, 2013;Schrödel et al, 2013;Yamamoto and Yuste, 2019)(see Box). During unrestrained animal movements, fast-tracking microscopes move to keep up with the animal as it swims or crawls (Nguyen et al, 2016;Venkatachalam et al, 2016;Cong et al, 2017;Kim et al, 2017b;Symvoulidis et al, 2017) (Figure 1a).…”
Section: Tools and Technologies To Observe Brain And Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…In smaller, transparent animals such as larval zebrafish, C. elegans, and hydra, activity of the majority of neurons can be imaged simultaneously at cellular resolution in the fully intact animal (Ahrens et al, 2013;Schrödel et al, 2013;Yamamoto and Yuste, 2019)(see Box). During unrestrained animal movements, fast-tracking microscopes move to keep up with the animal as it swims or crawls (Nguyen et al, 2016;Venkatachalam et al, 2016;Cong et al, 2017;Kim et al, 2017b;Symvoulidis et al, 2017) (Figure 1a).…”
Section: Tools and Technologies To Observe Brain And Behaviormentioning
confidence: 99%
“…The answer to this question depends heavily on the size and physical properties of the brain in question. Simultaneous whole-brain measurements of single-neuron activity have been acquired in small, transparent animals, notably the worm C. elegans (Schrödel et al, 2013), larval zebrafish (Ahrens et al, 2013), hydra (Yamamoto and Yuste, 2019) and perhaps soon in Drosophila (Mann et al, 2017). In mammals, recording electrophysiological activity across all cortical neurons is possible in principle (Kleinfeld et al, 2019), especially when allowing for recording techniques based on novel physical principles (Marblestone et al, 2013).…”
Section: Box: History and Future Of Large-scale Neural Recordingsmentioning
confidence: 99%
“…We assume that CBs are initiated by repeated stimulation of the fast pathway in a ring of muscle cells at the peduncle. What causes the CB nerve net to fire is still not known, although it is influenced by conditions such as osmolarity (Yamamoto and Yuste, 2019) , microbes (Murillo-Rincon et al, 2017) and temperature (Tzouanas et al, 2019) . While the CB nerve net is distributed, it has a high density of neurons at the peduncle and we assume these to be the primarysource of activation.…”
Section: Resultsmentioning
confidence: 99%
“…The rules that govern the generation of the neural activity are still an open question. Recent experiments have shown that temperature (Tzouanas et al, 2019) and osmolarity (Yamamoto and Yuste, 2019) can influence the CB firing rate in Hydra. Neural activity is likely to be influenced by the behavior or the state of the animal through mechanosensation and other sensory inputs.…”
Section: Discussionmentioning
confidence: 99%